Stress and its Consequence on Medical Students: A Cross Sectional Study at Medical College in Western India - Shreyash Mehta; Niraj Bharadva; Pravin Yerpude; Keerti Jogdand (Medsci Publications, 2018)
Background: A student in MBBS course commonly faces various kinds of stressors. This study was conducted to study the preva- lence of stress and its consequences in medical students of Gujarat Adani Institute of Medical Sciences (G.A.I.M.S.), Bhuj Material and Methods: This cross sectional study was conducted in 2015 using a self-administered questionnaire inspired from Kessler 10 psychological distress instrument (K10). Results: Out of 750 subjects, 213 students completed the question- naire. The prevalence of stress was 44.1% and it was highest among students of the third year part-II (49.25%), followed by stu- dents doing internship (49.01%), students in third year part- I(45.95%), students in second year (44.44%)and first year students (13.86%). There was statistically significant association between the language of study in pre-university level, student being hos- telite, performance in MBBS exams, attendance in classes and presence of stress. Conclusion: Such studies should do at every medical college and the stressors should be identified so timely action taken against it will prevent any effects caused on students. As we found out that the stress levels did increase with year of study, more support is required for the students in final year and medical colleges should stress-prevention strategies. Appropriate programmes for the rec- reation of the students must be developed to prevent the stress.